Heart rate variability and pre-competitive anxiety in BMX discipline - Mateo, M.; Blasco-Lafarga, C.; Martinez-Navarro, I.; Guzmán, J. F.; Zabala, M. (European Journal of Applied Physiology, 2012)
Altered neural mechanisms implying autonomic functioning have been described related to anxiety. Pre-competitive stress may be considered as an anxiety-state associated with disorders (i.e. somatic and cognitive alterations, and self-confidence worsening) that severely impair sport performance, conditioning short-lasting strength-related disciplines like BMX. From the psychological perspective, coaches use questionnaires like CSAI-2R to identify these alterations. However, with the emergence of psycho-physiological and non-linear approaches, recent studies suggest that HRV analysis provides a non-invasive tool to assess them. Hence, our purpose was to analyze how BMX competition affects subjective perception of anxiety, and if this emotional alteration is reflected in HR dynamics, analyzed both linear and nonlinearly, exploring the evolution of this relationship in a 2-day competition. Eleven male athletes from the BMX Spanish National Team were assessed from baseline HRV the morning of a training session (rT) and on two successive days of competition (rC1 and rC2), repeating HRV recording with CSAI-2R 20 min prior to training (aT) and competition (pre-competitive: aC1 and aC2). Repeated measures MANOVA showed significant vagal slow-down responses in aC1 and aC2 comparing not only with aT, but also comparing with rT, rC1 and rC2, coinciding with significant greater scores for the somatic and cognitive anxiety (SA and CA) in aC1 and aC2 versus aT. Pearson analysis showed a large and positive correlation between a1 and SA in C1, and close to it between SampEn and CA in aC2; both were confirmed by Bland-Altman chart analysis. Our results confirm that HRV analysis provide a complementary tool to assess competitive pressure.